YWCA's 75th anniversary celebration - Unknown:::Creator::::::::::::
Photograph shows two women socializing next to a food table with a large floral arrangement on it. They are each holding some food. There is a small crowd of women socializing behind them along a wall with a banner that reads: "YWCA Santa Clara Valley celebrates 75 years 1914-1989."